Survivorship of Bipolar Fresh Total Osteochondral Ankle Allograft. (March 2014) - Giannini, Sandro; Buda, Roberto; Pagliazzi, Gherardo; Ruffilli, Alberto; Cavallo, Marco; Baldassarri, Matteo; Vannini, Francesca
Background: Severe posttraumatic ankle arthritis poses a reconstructive challenge in the young and active patient. Bipolar fresh total osteochondral allograft (BFTOA) may represent an intriguing alternative to arthrodesis and prosthetic replacement. The purpose of this article was to evaluate the outcomes of BFTOA performed through an anterior approach to the ankle and to investigate the parameters influencing the results. Methods: A total of 26 patients (18 males and 8 females with a mean age of 34.9 ± 7.7 years) underwent BFTOA. The allograft was prepared with the help of specifically designed jigs and the surgery was performed using a direct anterior approach. Patients were evaluated clinically and radiographically at 2, 4, 6, and 12 months after the operation, and at a mean 40.9 ± 14.1 months of follow-up. Radiographic evaluation included the measurement of allograft size matching and alignment. Results: The AOFAS score improved from 26.6 ± 6 preoperatively to 77.8 ± 8.7 after a mean follow-up of 40.9 ± 14.1 months ( P < .0005). Six failures occurred. Joint degeneration was classified as 2 in 12 and as 3 in 14 patients. A statistically significant correlation between low degrees of distal tibial slope and better clinical outcomes was observed ( P = .049). Conclusion: BFTOA appears to be a viable option to arthrodesis or arthroplasty. Precise allograft sizing, stable fitting, and fixation and delayed weight-bearing were key factors for a successful outcome. In this series the correct alignment of the tibial graft, in terms of slope, was found to play a crucial role in the allograft survivorship. Level of Evidence: Level IV, case series.